2013
DOI: 10.1007/s13213-013-0724-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduced nitrite and biogenic amine concentrations and improved flavor components of Chinese sauerkraut via co-culture of Lactobacillus plantarum and Zygosaccharomyces rouxii

Abstract: The aim of this study was to investigate the effect of inoculated fermentation on the quality of Chinese sauerkraut. To this end we studied a co-culture system consisting of Lactobacillus plantarum Shanghai brewing 1.08 and Zygosaccharomyces rouxii CGMCC 3791 during inoculated sauerkraut fermentation. The nitrite concentrations in pickled cabbage and radish inoculated with starter cultures of L. plantarum and Z. rouxii were significantly lower than those in the spontaneous fermentation system during the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Although ketones are common in fermented foods, those identified in the current study have never been reported previously, and include D-camphor, 3hexanone, and (-)-camphor. Of the acids detected here, 2-Methyl-Propanoic acid has been found in Chinese sauerkraut and fermented radishes (Wu et al, 2014), while nonanoic acid mainly contributes to the oily notes in fermented vegetables and has been identified in pickled chilis (Xiao et al, 2010). Furthermore, phenols are responsible for smokey and phenolic odors, but the presence of 3,5-Di-tert-Butylphenol and 2,6-Di-tert-butyl-4methylphenol have never been reported previously.…”
Section: Discussionmentioning
confidence: 55%
“…Although ketones are common in fermented foods, those identified in the current study have never been reported previously, and include D-camphor, 3hexanone, and (-)-camphor. Of the acids detected here, 2-Methyl-Propanoic acid has been found in Chinese sauerkraut and fermented radishes (Wu et al, 2014), while nonanoic acid mainly contributes to the oily notes in fermented vegetables and has been identified in pickled chilis (Xiao et al, 2010). Furthermore, phenols are responsible for smokey and phenolic odors, but the presence of 3,5-Di-tert-Butylphenol and 2,6-Di-tert-butyl-4methylphenol have never been reported previously.…”
Section: Discussionmentioning
confidence: 55%
“…Wu et al . (2014a) also reported that starter inoculation ( L. plantarum and Zygosaccharomyces rouxii ) increased esters in Chinese sauerkraut compared with naturally fermented sauerkraut. In the present study, esters were most dominant and increased in both HD1.7‐inoculated and control samples as the fermentation progressed.…”
Section: Resultsmentioning
confidence: 93%
“…Acidity was determined based on the method described by Wu et al . (,b) Lactic acid was used as standard and measured by titration with sodium hydroxide and its reduction coefficient was 0·09.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations